(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article reveals the features of education speech voice actors puppet theater. Makes recommendations for recognizing professional aptitude voice data entrants branch "of the puppet theater actor." Also talks about the different systems and methods for their dolls "sound."